30 ELEVATION OF PLASMA ONCOSTATIN M IS ASSOCIATED WITH PRIMARY BIOCHEMICAL NONRESPONSE AND SECONDARY CLINICAL NONRESPONSE TO INFLIXIMAB IN PEDIATRIC CROHN'S DISEASE PATIENTS. (7th February 2019) - Minar, Phillip; Lehn, Christina N; Tsai, Yi-Ting; Jackson, Kimberly; Denson, Ted
Abstract: Background: Oncostatin M (OSM) and OSM receptor (OSMR) were found to be highly expressed in inflamed intestinal tissue in patients with Crohn's disease (CD) and ulcerative colitis (UC). 1 West et al. also found elevations of mucosal OSM was strongly associated with treatment nonresponse to tumor necrosis factor-α inhibitors (anti-TNF). 1 We hypothesized that increased abundance of plasma OSM would also be associated with anti-TNF nonresponse with our primary aim to identify an OSM cut-point for early anti-TNF nonresponse. Methods: We enrolled anti-TNF naïve children with CD starting infliximab into this prospective, observational study. The primary outcome was biochemical response and defined by a fecal calprotectin <400 µg/ml prior to the first maintenance dose (infusion 4). This outcome was restricted to patients with both a pre-infliximab fecal calprotectin >400 µg/ml and a stool sample collected at infusion 4. Clinical remission at 12 months was defined as a weighted pediatric CD activity index <12.5, off steroids, and on infliximab without surgery in the first year. The ideal OSM cut-point was identified using the Youden index from the receiver operating characteristic curve analysis of biochemical responders and nonresponders. OSM was measured using ELISA (ThermoFisher, Frederick, MD) with an intra-assay CV<10%. Fecal calprotectin was measured with ELISA (Buhlmann, Switzerland). Infliximab concentrations were measured with ELISA (Immundiagnostik, Germany). Results: We measured pre-infliximab OSM in 40 consecutive CD patients. The cohort was 35% female, 90% white race with a mean age of 13 (SD 4) years at the start of infliximab. One patient remained on methotrexate during induction and 50% of the cohort received prednisone prior to the first induction dose. 33/40 met criteria for evaluation for the primary aim with 16/33 (49%) in biochemical remission at infusion 4. The median (IQR) OSM in biochemical nonresponders was 96 (69-198) pg/ml compared to 166 (84-1766) pg/ml in nonresponders (p=0.035, Figure1). Using the Youden index, we identified plasma OSM >143 pg/ml was 71% sensitive and 75% specific for biochemical nonresponse (Figure 2). The median infusion 4 fecal calprotectin in the OSMhigh (>143 pg/ml) group was 985 (382-2501) µg/g compared to 317 (141-676) µg/g in OSMlow group (p=0.04). We found only 25% of the OSMhigh patients achieved biochemical response compared to 71% with OSMlow (p=0.015). Thirty-five percent of OSMhigh patients achieved steroid-free clinical remission at month 12 (odd's ratio of 0.21, 95% CI 0.05-0.77, p=0.023). We found no differences in infliximab concentration at infusions 2, 3 and 4 between OSMhigh and OSMlow patients. Conclusions: In a small pediatric CD cohort, we identified a pre-infliximab cut-point of >143 pg/ml was predictive of early biochemical nonresponse and secondary clinical nonresponse at year 1. Figure 1. Oncostatin M (OSM) was measured with ELISA prior to the first infliximab infusion. Fecal calprotectin was measured prior to infusion 1 and 4. Groups compared by Mann-Whitney test. Figure 2. Oncostatin M (OSM) was measured prior to the first infliximab infusion. Area under the curve (AUC) was determined by the receiver operating characteristic curve for biochemical nonresponse at infusion 4 (defined by a fecal calprotectin ≥400 µg/g). The ideal cut-point for OSM was determined by the Youden index.